Ligand activation leads to regulated intramembrane proteolysis of fibroblast growth factor receptor 3 - Degnin, Catherine R. (The American Society for Cell Biology, 2011)
Fibroblast growth factor receptor 3 (FGFR3) is a major negative regulator of bone growth that inhibits the proliferation and differentiation of growth plate chondrocytes. Activating mutations of its c isoform cause dwarfism in humans; somatic mutations can drive oncogenic transformation in multiple myeloma and bladder cancer. How these distinct activities arise is not clear. FGFR3 was previously shown to undergo proteolytic cleavage in the bovine rib growth plate, but this was not explored further. Here, we show that FGF1 induces regulated intramembrane proteolysis (RIP) of FGFR3. The ectodomain is proteolytically cleaved (S1) in response to ligand-induced receptor activation, but unlike most RIP target proteins, it requires endocytosis and does not involve a metalloproteinase. S1 cleavage generates a C-terminal domain fragment that initially remains anchored in the membrane, is phosphorylated, and is spatially distinct from the intact receptor. Ectodomain cleavage is followed by intramembrane cleavage (S2) to generate a soluble intracellular domain that is released into the cytosol and can translocate to the nucleus. We identify the S1 cleavage site and show that γ-secretase mediates the S2 cleavage event. In this way we demonstrate a mechanism for the nuclear localization of FGFR3 in response to ligand activation, which may occur in both development and disease.